NUCLEOPHILIC RING-OPENING OF EPOXIDES BY ORGANOLITHIUM COMPOUNDS - AB-INITIO MECHANISMS - Harder, Sjoerd; van Lenthe, Joop; van Eikema Hommes, Nico; Schleyer, Paul (Journal of the American Chemical Society, 1994)
Ab initio calculations (MP4/6-31+G*//6-31+G*+DELTAZPE) have been performed on the ring-opening reaction of ethylene oxide by monomeric and dimeric lithium hydride and by dimeric methyllithium, both with retention and with inversion of configuration at the carbon being attacked. Several highly ionic transition structures were located. The large preference for reaction with inversion is due to the higher degree of rupture of the C-O bond in the retention transition structure. Cationic assistance, i.e. Li+ coordination to the epoxide oxygen, significantly lowers the activation energies. An intermolecular push-pull mechanism, or an intramolecular mechanism in which the lithium aggregate is opened to form a chain, is proposed for reaction in moderately polar solvents.